2014
DOI: 10.1371/journal.pgen.1004569
|View full text |Cite
|
Sign up to set email alerts
|

The Not5 Subunit of the Ccr4-Not Complex Connects Transcription and Translation

Abstract: Recent studies have suggested that a sub-complex of RNA polymerase II composed of Rpb4 and Rpb7 couples the nuclear and cytoplasmic stages of gene expression by associating with newly made mRNAs in the nucleus, and contributing to their translation and degradation in the cytoplasm. Here we show by yeast two hybrid and co-immunoprecipitation experiments, followed by ribosome fractionation and fluorescent microscopy, that a subunit of the Ccr4-Not complex, Not5, is essential in the nucleus for the cytoplasmic fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 55 publications
4
92
0
1
Order By: Relevance
“…Previous studies have shown that Not5 is required for association of Not1 to specific mRNAs (Villanyi et al, 2014) and that in the absence of Not5 the expression of nuclear encoded mitochondrial protein mRNAs was upregulated (Azzouz et al, 2009b; Cui et al, 2008). In not5Δ Not1 interaction with most other Ccr4-Not subunits is reduced (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Not5 is required for association of Not1 to specific mRNAs (Villanyi et al, 2014) and that in the absence of Not5 the expression of nuclear encoded mitochondrial protein mRNAs was upregulated (Azzouz et al, 2009b; Cui et al, 2008). In not5Δ Not1 interaction with most other Ccr4-Not subunits is reduced (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent finding that Not5 is necessary for cytoplasmic functions of Rpb4 suggested that the multisubunit Ccr4-Not complex might also play a key role in regulating the gene expression circuitry (Villanyi et al, 2014). Ccr4-Not is a conserved multifunctional eukaryotic regulator composed of nine subunits in the yeast S.cerevisiae .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of these cases, buffering is likely mediated by proteins that function at multiple levels of gene expression. For example, the yeast RNA binding protein Rpb4 appear to affect both transcription and translation, as do the CCR4/Not complex and Not5 ref 75. .…”
Section: New Insights Into Gene Expression Regulationmentioning
confidence: 99%
“…Recently, the CCR4-NOT complex has also been shown to regulate transcription elongation (Kruk et al 2011;Dutta et al 2015) and cotranslational quality control by its associated ubiquitin E3 ligase activity (for review, see Panasenko 2014). The CCR4-NOT complex has been implicated in the promoter-mediated coordination of transcription and mRNA decay by interacting with the Rpb4/7 subunits of RNA polymerase II (Lotan et al 2005;Villanyi et al 2014). The CCR4-NOT complex is assembled around the CNOT1 subunit, which serves as a scaffold and interacts with various modules.…”
mentioning
confidence: 99%